The Application of Botanical Pesticides to Control Fusarium Wilt on Asparagus Beans - Adiwena, Muh.; Murtilaksono, Aditya; Ngau, Mikael; Rachmadaniar, Rachmadaniar; Egra, Saat; Pradana, Ankardiansyah Pandu; Yousif, Ahmed Ibrahim Alrashid (Green Engineering Society, 2024)
Triggered by a fungus of the genus Fusarium, wilting prevails in various horticultural crops in Indonesia. In asparagus beans, this pathogen can lead to decreased production. One eco-friendly controlling measure is the application of botanical pesticides made from betel leaves and neem leaves which have been extensively used to control various pathogenic fungi. This study aims to evaluate the effectiveness of plant-based pesticides made from neem and betel leaves in controlling Fusarium wilt in asparagus beans. This research was run for approximately six months, initiated at the Laboratory of Plant Protection in Universitas Borneo Tarakan, and ended in the Experimental Garden of the Faculty of Agriculture. It involved Fusarium propagation, preparation of planting media, planting asparagus beans, infecting Fusarium, and producing as well as applying botanical pesticides. It employed a one-factor randomized block design with 5 treatments, control (P0), 5% neem leaf extract per plant (P1), 10% neem leaf extract per plant (P2), 5% betel leaf extract per plant (P3) and 10% betel leaf extract per plant (P4). The covariance analysis results showed that the treatment did nothave a significant effect on the number of affected branches, the number of pods and pod weight. Even so, it can be concluded that P2 can reduce wilted branches by up to 48%, with the same concentration, and P4 can reduce wilted branches by up to 52%. In terms of the total number and the total weight of the pods, P4 achieved the best results with 77 pods, weighing 3,272 grams.